The peculiarities of the way to study and programming of modern microcontrollers - Конюшко, В.М. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2012)
The possibility to improve the training process in order to study modern microcontrollers and to develop application programs for them.